What are the Broken Clocks within your organization? - Stephanie D. Gingerich (Interdisciplinary Journal of Partnership Studies, 2020)
The author reflects on the value of partnership approaches to ensure that the Broken Clocks, or gaps that become background to those immersed in the work within each organization, are identified for improvement. Incorporating partners who encounter the physical space with varying perspectives can bring the Broken Clocks back to life once again.